Gestión del talento humano y su influencia en la productividad de los colaboradores de la empresa Agrolmos S.A. 2017 - Moreno Vásquez, Erica Jaquelin (2018)
The following investigation has like general objective to determine the relation between the management of the human talent and the productivity of the collaborators of the company Agrolmos S.A. The research design is non-experimental - correlational, that is, this design allowed the description of the study variables, in a single moment. Two instruments were used to measure the two variables: the instrument to measure human talent management has 05 dimensions and 19 items and the instrument to measure productivity has 03 dimensions and 20 items. It was determined that the management of human talent if it has a direct relationship with the productivity of the employees of the company Agrolmos S.A. so the hypothesis proposed in the study is accepted. It was found that 22.84% of the employees indicate that the management of human talent in the company Agrolmos is very bad, 30.92% indicate that it is bad, 25.82% indicate that it is good and 20.42% indicate that it is very good. It was determined that the level of productivity of the employees of the Agrolmos company is very good at 19.74%, good at 24.16%, bad at 29.24% and very bad at 26.86%.